The Translation Problem Types in Translating Indonesia Text to English (A Case Study of Translation Subject of Fifth Semester English Students –UPY) - Sujatmiko, Sujatmiko (ELTICS : Journal of English Language Teaching and English Linguistics, 2017)
This research is entitled “The Translation Problem  Types in Translating Indonesia text into English (A Case Study of Translation Subject of Fifth Semester English Department – UPY) . It is about how Indonesia text is translated into English by English students, to identify the translation problems, and to identify the problematics of translation technique. This research uses qualitative method to analyze the data. Techniques of analyzing data in this research consist of 3 components, they are (1) reducing the data, (2) explaining the data, and (3) taking a conclusion. Reducing data is a process of selecting, focusing, simplifying and abstracting the data. Explaining the data is a process of organizing information and arranging the complete narration. Taking a conclusion is a process of drawing conclusion from the data. The data source of this research areIndonesia text and student’s translation. After conducting the research, the research find the data that all respondents have similar translation problem types in translating Indonesia text into English. The problems are diction, tenses, no equivalence translation; others have problems of adverb, article, and relative clause. None of respondents apply other translation technique. They only apply word per word translation technique. The accuracy of transfer level is adequate level. Only one respondent have almost completely successful transfer level. Other respondents have adequate accuracy transfer level. By applying the untrue translation technique has an impact to translation accuracy transfer level. This research is expected to open wide opportunities and challenges to academicians, especially those in translation linguistics sphere to deepen their research and study, especially in translating Indonesia text to English in order to be a new contribution to the translation fields. Keywords : Translation Problem, Technique, Student’s Translation